Analysis Of The Rising Temperature Of Lubricated Oil On Auxiliary Machinery At KMP. PORTLINK - Noor Sulistiyono; Sri Kelana; Muhammad Raken Al Zuhra (IWJ : Inland Waterways Journal, 2022)
In the operation of the auxiliary motor, there will be continuous rotation and cause friction, so it will generate heat. To avoid more heat, a liquid substance is used, namely lumas oil. These observations were made on board the KMP. Portlink Nine months, namely from October 5, 2021 to July 05, 2022.Researchers use qualitative methods, observations, interviews and literature studies. researchers analyze the causative factors, and how to deal with the rising temperature of the auxiliary machine's lumas oil. The data obtained from this observation shows that there is an increase in the temperature of lubricating oil in auxiliary machines caused by ineffective heat absorption at lubricating oil coolers and abnormal seawater pressure caused by the clogging of the Streiners Sea Chest filter, from the results of the study obtained a temperature increase on May 22, 2022 at guard hours 20.00-24.00 where the temperature reaches a temperature of 85 ° C and a pressure of 2.5 bar.